Student satisfaction with the Service-Learning methodology: an added value in the training of the nursing degree - García Garcés, Laura; Ruiz-Zaldibar, Cayetana; Gerónimo Llopis, Ángel; Vicario Merino, Ángel; Lluesma Vidal, Marta (Horizonte Sanitario, 2021)
Objective: To evaluate the effect on the satisfaction of nursing students and the participants of Service-Learning methodology in the development of Health Education workshops. Method: Service-Learning project was designed in four stages: 1) students training in knowledge about Community Nursing and Health Education; 2) development of healthy workshops for its implementation in associations; 3) implementation of the workshops; 4) reflection on Service-Learning impact. An ad hoc questionnaire was developed to assess students’ satisfaction. It was also evaluated the workshops’ participant’s satisfaction. Results: students reported having a very high level of satisfaction by increasing their scores after improving Service-Learning methodology in the subject. In addition, participants who received health promotion workshops developed by nursing students reported a positive impact on their health. Conclusion: development of Service-Learning methodology associated with health education implies high level of satisfaction in nursing students and a social impact for the community.